China off center : mapping the margins of the middle kingdom - Blum, Susan Debra; Jensen, Lionel M. (University of Hawai'i Press, 2002)
Annotation China Off Center takes as its fundamental assumption that contemporary China can only be understood as a complex, decentralized place, where the view from above (Beijing) and from tourist buses is a skewed one. Instead of generalizing about China, it demonstrates that this diverse national terrain is better conceived as it is experienced by Chinese, as a set of many Chinas. To that end, this anthology of interpretive essays and ethnographic reports focuses on the everyday, the particular, the local, and the puzzling. Among the many topics covered are ethnic minorities, linguistic diversity, competing regional loyalties, sexuality, gender and work, the floating populations, rock and roll, qigong (spiritual and martial arts), and popular religion. Together with contextualizing introductions, the readings provide students with a compelling look at some little-known but significant aspects of China from the past decade; for those already familiar with China, they furnish an assortment of uncommon viewpoints in a single, convenient volume.